Lucy Letby: Three senior hospital bosses arrested on suspicion of gross negligence manslaughter - Dyer, Clare (BMJ. British medical journal (Clinical research ed.), 2025)
Three former senior leaders at the NHS hospital where the neonatal nurse Lucy Letby worked have been arrested on suspicion of gross negligence manslaughter. Letby is serving 15 whole life terms in prison after being convicted of murdering seven babies and attempting to murder seven others, one of them twice, while working at the hospital. A public inquiry, chaired by Court of Appeal judge Kathryn Thirlwall, into the circumstances concerning Letby’s crimes heard evidence from the senior leadership team and is due to report early next year. 1 Dyer C. Letby case: